Exchange rates and individual good's price misalignment: Some preliminary evidence of long-horizon predictability - Wei Dong; Deokwoo Nam (Bank of Canada, 2011)
When prices are sticky, movements in the nominal exchange rate have a direct impact on international relative prices. A relative price misalignment would trigger an adjustment in consumption and employment, and may help to predict future movements in the exchange rate. Although purchasing-power-parity fundamentals, in general, have only weak predictability, currency misalignment may be indicated by price differentials for some goods, which could then have predictive power for subsequent re-evaluation of the nominal exchange rate. The authors collect good-level price data to construct deviations from the law of one price and examine the resulting price-misalignment model's predictive power for the nominal exchange rates between the U.S. dollar and two other currencies: the Japanese yen and the U.K. pound. To account for small-sample bias and data-mining issues, inference is drawn from bootstrap distributions and tests of superior predictive ability (SPA) are performed. The slope coefficients and R-squares increase with the forecast horizon for the bilateral exchange rates between the U.S. dollar and the Japanese yen and the U.S. dollar and the U.K. pound. The out-of-sample SPA tests suggest that the authors' price-misalignment model outperforms random walks either with or without drift for the U.S. dollar vis-à-vis the Japanese yen at the 5 per cent level of significance over long horizons.
Keywords: F31; F47; 330; Exchange rates; International topics; Preisrigidität; Wechselkurs; Internationaler Preiszusammenhang; Kaufkraftparität; USA; Japan; Großbritannien